Use of Non–Vitamin K Antagonist Oral Anticoagulants in Atrial Fibrillation Patients with Malignancy: Clinical Practice Experience in a Single Institution and Literature Review - Russo, Vincenzo; Rago, Anna; Papa, Andrea Antonio; Meo, Federica Di; Attena, Emilio; Golino, Paolo; D'Onofrio, Antonio; Nigro, Gerardo (Seminars in Thrombosis and Hemostasis, 2018)
This observational study aimed to investigate the efficacy and safety of non–vitamin K antagonist oral anticoagulants (NOACs) in atrial fibrillation (AF) patients with malignancy. A total of 76 patients (mean age: 73.2 ± 8.9; 28 females) with AF and malignancy treated with NOAC were included in the analysis. The mean CHA2DS2-VASc and HAS-BLED scores were 3.2 ± 1.2 and 2.2 ± 0.9, respectively. The study population was taking dabigatran 150 mg (25%) twice daily (BID), apixaban 5 mg BID (25%), dabigatran 110 mg BID (24%), rivaroxaban 20 mg (18%) once a day (OD), rivaroxaban 15 mg OD (5%), or apixaban 2.5 mg OD (3%). NOAC therapy began, on average, 248 ± 238 days before malignancy diagnosis for an average duration of 1,000 ± 289 days. Stroke, transient ischemic attack, major and minor bleeding events, other adverse effects, and major cardiovascular complications during the follow-up period were collected. In our study population, no patients experienced thromboembolic events during therapy with any NOAC. We recorded a low global incidence of major bleeding (3.9%) with a mean annual incidence of 1.4%. No hemorrhagic stroke or subarachnoid hemorrhage was observed. Only nine patients (11.8%) experienced minor bleeding. According to our data, anticoagulation therapy with NOACs seems to be an effective and safe treatment strategy for nonvalvular AF patients with malignancy.
Keywords: atrial fibrillation; cancer; NOAC; clinical practice; dabigatran; apixaban; rivaroxaban; malignancy; stroke; bleeding; safety; efficacy